Performance analysis of IIR filter in removing PLI from EEG signal - Habib Jibon, Rayhan; Podder, Etu; Al-Mamun Bulbul, Abdullah; Nath Bairagi, Ramendra; Salim Ahmed, Md.; Ahmmed Shohagh, Imtiaj (International Journal of Engineering and Technology, 2019)
Electroencephalogram (EEG) is a non-incursive test and the electrical signals of the brain from the scalp is recorded by this test. Several diagnosis conditions (for example dizziness, epilepsy, head injuries, etc.) are checked by this test. Moreover, the information about the brain death is also be acquainted by the EEG test. EEG signals inherit the bandwidth of 1 to 50 Hz. So, these can be easily contaminated by different artifacts (such as power line interference (PLI), eye blink artifact, and electromyogram artifact). Out of these artifacts, 50 Hz PLI is the most salient. In this paper, IIR filters (Notch filter and Chebyshev type II filter) are configured to remove the PLI. Through the subsequent utilization of these filters, the artifact can be removed from the EEG signals in a notable amount. Thereby this approach will ensure the true information about detecting brain diseases and possibilities to know how many portions of the main signal is released from the artifact. Investigating the simulation results that includes the output waveforms and SNR values, it can be concluded that the Notch filter performs better than Chebyshev type II filter. This paper presents a comparison between two digital (Notch, Chebyshev type II) filters for removing PLI from EEG signal and helps to choose the best one from these two filters.Â Â